Granting Clemency to Antasari Azhar as the Object of a State Administrative Law Dispute - Ary Muktian Syah; Pratama Herry Herlambang; Bayangsari Wedhatami; Chirstoverus Marco (Universitas Negeri Semarang, 2023)
This study provides an overview of the state administrative law dispute surrounding the granting of clemency to Antasari Azhar, a prominent figure involved in a high-profile legal case. The controversy stems from the exercise of executive power and the application of clemency within the framework of state administrative law. Antasari Azhar, a former Indonesian Corruption Eradication Commission (KPK) chairman, was convicted in a notable corruption case. Subsequently, his request for clemency sparked debates, legal challenges, and concerns about the integrity of the administrative process. This study delves into the legal dimensions of Antasari Azhar’s clemency case, examining the constitutional and administrative law aspects involved. Key issues include the discretionary powers of the executive in granting clemency, the potential influence of political considerations, and the adherence to legal procedures during the decision-making process. The research aims to shed light on the broader implications of this case for the rule of law, the separation of powers, and the accountability of public officials. Through a comprehensive analysis of relevant legal frameworks, court decisions, and scholarly perspectives, this study seeks to contribute to the understanding of the complex interplay between executive powers and the legal principles governing clemency in the context of state administrative law. Furthermore, it addresses the implications of such disputes for the overall legal and political landscape, emphasizing the importance of transparency, due process, and accountability in the exercise of executive clemency.